Defective antigen-presenting cell function in human neonates (2006)
ABSTRACT: Immaturity of the immune system has been suggested as an underlying factor for the high rate of morbidity and mortality from infections in newborns. Functional impairment of neonatal T cells is frequently quoted as the main underlying mechanism for such immaturity. However, recent studies suggest that neonatal antigen-presenting cells (APCs) also exhibit functional alterations, which could lead to secondary defects of adaptive T cell responses. In this review, we summarize what is known on the functionality of APC at birth and during early childhood. Compared to adults, neonatal APCs display markers of immaturity and produce low levels of cytokines. Multiple factors could be involved in neonatal APC alteration, such as intrinsic immaturity, defective interaction between APCs and T cells, and regulatory T cell-mediated inhibition. Characterization of the relative contribution of each mechanism is clearly needed to better understand the functional capability of the neonatal immune system.